Records of a Family of Engineers - Stevenson, Robert Louis, 1850-1894 (Salt Lake City, UT : Project Gutenberg, 1995)
"Records of a Family of Engineers" by Robert Louis Stevenson is a historical account written in the early 20th century. The book delves into the lineage of the Stevenson family, particularly focusing on their contributions as engineers and their experiences across generations in Scotland, intertwining personal anecdotes with broader historical narratives. The opening of the book introduces the reader to the Stevenson family tree, tracing their surname's evolution and historical context from the 13th century onward. It reveals a lineage that has faced both successes and tragedies, with a particular focus on the early lives of James Stevenson, his brother Hugh, and their heir, Robert Stevenson. The text sketches their aspirations, marriages, and struggles, ultimately painting a portrait of a family deeply rooted in the engineering profession, set against the backdrop of the rugged Scottish landscape and societal changes of their time. This initial section not only captures the essence of their individual experiences but sets the stage for further exploration of the family's lasting impact on engineering. (This is an automatically generated summary.)
Release date is 1995-06-01
Transcribed from the 1912 Chatto & Windus edition by David Price. Additional proofing by Peter Barnes
Keywords: Stevenson, Robert, 1772-1850; Stephenson family; Engineers -- Great Britain -- Biography; Bell Rock Lighthouse (Scotland); Lighthouses -- Scotland